Probing the mechanism for hydrogel-based stasis induction in human pluripotent stem cells: is the chemical functionality of the hydrogel important?. Issue 1 (14th November 2019) - Sponchioni, M.; O'Brien, C. T.; Borchers, C.; Wang, E.; Rivolta, M. N.; Penfold, N. J. W.; Canton, I.; Armes, S. P.
Abstract : It is shown that hydroxyl functionality is required to induce stasis in human embryonic stem cell colonies immersed within wholly synthetic block copolymer worm gels with comparable storage moduli. Thus gel softness does not appear to be an essential parameter for stasis induction. Abstract : It is well-known that pluripotent human embryonic stem cells (hPSC) can differentiate into any cell type. Recently, we reported that hPSC colonies enter stasis when immersed in an extremely soft hydrogel comprising hydroxyl-functional block copolymer worms (I. Canton, N. J. Warren, A. Chahal, K. Amps, A. Wood, R. Weightman, E. Wang, H. Moore and S. P. Armes, ACS Centr. Sci., 2016, 2, 65–74). The gel modulus and chemical structure of this synthetic hydrogel are similar to that of natural mucins, which are implicated in the mechanism of diapause for mammalian embryos. Does stasis induction occur merely because of the very soft nature of such hydrogels or does chemical functionality also play a role? Herein, we address this key question by designing a new hydrogel of comparable softness in which the PGMA stabilizer chains are replaced with non-hydroxylated poly(ethylene glycol) [PEG]. Immunolabeling studies confirm that hPSC colonies immersed in such PEG-based hydrogels do not enter stasis but instead proliferate (and differentiate if no adhesion substrate is present). However, pluripotency is retained if an appropriate adhesion substrate is provided. Thus, the chemical functionality of the hydrogel clearly plays a decisive role in the stasis induction mechanism.